Patients' satisfaction on primary healthcare services in China and its associated factors during COVID-19 pandemic: a cross-sectional study - Li, Huan; Swe, Kye Mon Min; Jabbar, Mohammed Abdulrazzaq; Ching, Siew Mooi (Academy of Family Physicians of Malaysia, 2023)
Introduction: The provision of a satisfactory service by community healthcare centres in China plays an important role in the prevention and control of communicable diseases, especially during the COVID-19 pandemic. However, there is a lack of study in this field. This study aimed to determine the level of patient satisfaction with primary healthcare services in China and its associated factors during the COVID-19 pandemic. Methods: This cross-sectional study was conducted at 10 primary healthcare clinics in Xi’an, China. The 18-Item Patient Satisfaction Questionnaire was used for data evaluation and SPSS version 23.0 for data analysis. Results: A total of 315 patients were recruited. The overall patient satisfaction score was 26.1±3.1. In the multiple linear regression analysis, the highly educated patients had a higher patient satisfaction score than the low-educated patients (β=1.138, 95% confidence interval=0.135–2.141, P=0.026). Conclusion: The overall patient satisfaction level of the patients who attended community healthcare centres in Xi’an was high. The patients with a higher educational level showed a higher patient satisfaction level than did those with a lower educational level.